Implications of Recent Revelations from Basic and Clinical Studies of Barrett's Esophagus for Screening and Surveillance Strategies. Issue 1 (March 2021) - Spechler, Stuart Jon; Souza, Rhonda F.
During the past several decades, while the incidence of esophageal adenocarcinoma (EAC) has risen dramatically, our primary EAC-prevention strategies have been endoscopic screening of individuals with GERD symptoms for Barrett's esophagus (BE), and endoscopic surveillance for those found to have BE. Unfortunately, current screening practices have failed to identify most patients who develop EAC, and the efficacy of surveillance remains highly questionable. We review potential reasons for failure of these practices including recent evidence that most EACs develop through a rapid genomic doubling pathway, and recent data suggesting that many EACs develop from segments of esophageal intestinal metaplasia too short to be recognized as BE. We highlight need for a biomarker to identify BE patients at high risk for neoplasia (who would benefit from early therapeutic intervention), and BE patients at low risk (who would not benefit from surveillance). Promising recent efforts to identify such a biomarker are reviewed herein.